2019
DOI: 10.1111/gwmr.12338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salix Genotypes for Co‐Phytofiltration of Iron and Manganese from Simulated Contaminated Groundwater in a Floating Culture System

Abstract: Groundwater contamination with iron (Fe) and manganese (Mn) is directly related to drink water safety. It remains challenging to simultaneously remove Fe and Mn from groundwater by conventional physical and chemical methods. Willows (Salix spp.) show promise for co‐phytofiltration of Mn and Fe from groundwater. Here, a floating culture system was developed using willows for co‐phytofiltration of Mn and Fe from simulated groundwater. Genotypic differences of willows were evaluated in terms of their tolerance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…They observed 83.20, 37.50, and 17.67% Fe removal efficiency after 32 days at 5, 10, and 15 mg L −1 concentration, respectively. In another case, Yang et al (2019) reported co‐phytofilteration potential of willows for accumulation and translocation of Mn and Fe. They observed that, J842 ( S .…”
Section: Remediation Of Fementioning
confidence: 99%
“…They observed 83.20, 37.50, and 17.67% Fe removal efficiency after 32 days at 5, 10, and 15 mg L −1 concentration, respectively. In another case, Yang et al (2019) reported co‐phytofilteration potential of willows for accumulation and translocation of Mn and Fe. They observed that, J842 ( S .…”
Section: Remediation Of Fementioning
confidence: 99%